Polymorphisms of drug-metabolizing enzyme CYP2E1 in Chinese Uygur population. Issue 7 (February 2018) - Zhu, Linhao; He, Yongjun; Niu, Fanglin; Yan, Mengdan; Li, Jing; Yuan, Dongya; Jin, Tianbo
Abstract : Abstract: Pharmacogenetics is the genetic basis of pharmacokinetics, genetic testing, and clinical management in diseases. Evaluation about genetic alterations of drug metabolizing enzymes in human genome contributes toward understanding the interindividual and interethnic variability for clinical response to potential toxicants. CYP2E1 gene encodes a drug-metabolizing enzyme that metabolizes mostly small, polar molecules, including toxic laboratory chemicals. The aim of this study was to investigate CYP2E1 polymorphisms and gene profile in a Chinese Uygur population. Frequencies for the CYP2E1 mutated alleles and genotypes were screened in 100 unrelated random healthy Uygur volunteers. PCR and direct sequencing revealed a total of 32 polymorphisms, of which 5 novel mutations were presented. Rs 943975 was the most common single nucleotide polymorphism (SNP). The allele frequencies of CYP2E1 * 1A, * 4, * 7A, and * 7C were 65.5, 2, 19.5, and 13%, respectively. The most common genotype combinations were CYP2C19 * 1A/ * 1A (43%) and * 1A/ * 7C (24%). Functional prediction for 2 nonsynonymous mutations G173S and V179I was performed using MutationTaster, sorting intolerant from tolerant, and PolyPhen-2. The observations of the present study give rise to useful information on CYP2E1 polymorphisms in Chinese Uygur individuals. The results suggest important clinical implications for the use of medications metabolized by CYP2E1 among Uygurs.